Innovation as an expansion strategy to the African Continent: the case of Sumol+Compal in Angola - Neves, João Pedro Cordeiro (2019)
This study will present several expansion strategies to Angola that will help SUMOL+COMPAL growing in dimension and operational profit. Given the delicate economic situation that Angola currently faces, the solutions presented will help overcoming such difficulties. These were formulated using qualitative methods (interviews) and a documentary analysis. This thesis firstly explored a contextualizing approach, followed by some practical cases and concluding with the five recommendations: Nutrient Water, Múcua Juice, Isotonic Drinks, Exportation of Drinks to Congo and Agricultural Process. The implications of these solutions were described by a board member as excellent contributes for the company